Adjustment in EMU: Is Convergence Assured? - Sebastian Dullien; Ulrich Fritsche; Ingrid Groessl; Michael Paetz (Hamburg University, Department Economics and Politics, 2009)
Using a modified version of the model presented by Belke and Gros (2007), we analyze the stability of adjustment in a currency union. Using econometric estimates for parameter values we check the stability conditions for the 11 original EMU countries and Greece. We found significant instability in the model for a large number of countries. We then simulate the adjustment process for some empirically observed parameter values and find that even for countries with relatively smooth adjustment, the adjustment to a price shock in EMU might take several decades.
Keywords: E32; E61; C32; 330; EMU; convergence; stability; inflation